2017
DOI: 10.1016/j.jtcvs.2017.05.066
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of aortic dissection smooth muscle cell phenotype switch

Abstract: Our study suggests that NANOG is highly expressed in TAD aortic wall and VSMCs. Increased NANOG promotes VSMCs phenotype switch by directly up-regulating OPN through binding to its promoter region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…In the pathogenesis of TAD, vascular smooth muscle cells (VSMCs) play an important role in the process of aortic wall contraction and synthesis in the presence of the stimulation of various cells to promote vascular remodeling [5]. With the phenotypic change, VSMCs transform from contraction (differentiation) phenotype to synthesis (dedifferentiation) phenotype [6,7]. Dedifferentiated VSMCs showed higher viability in terms of proliferation, migration and synthesis, and at the same time, the expressions of differentiation markers α-SMA and SM22α were down-regulated [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the pathogenesis of TAD, vascular smooth muscle cells (VSMCs) play an important role in the process of aortic wall contraction and synthesis in the presence of the stimulation of various cells to promote vascular remodeling [5]. With the phenotypic change, VSMCs transform from contraction (differentiation) phenotype to synthesis (dedifferentiation) phenotype [6,7]. Dedifferentiated VSMCs showed higher viability in terms of proliferation, migration and synthesis, and at the same time, the expressions of differentiation markers α-SMA and SM22α were down-regulated [6].…”
Section: Introductionmentioning
confidence: 99%
“…With the phenotypic change, VSMCs transform from contraction (differentiation) phenotype to synthesis (dedifferentiation) phenotype [6,7]. Dedifferentiated VSMCs showed higher viability in terms of proliferation, migration and synthesis, and at the same time, the expressions of differentiation markers α-SMA and SM22α were down-regulated [6]. In addition, ECM is the main component that forms the morphology of the aortic blood vessel wall, and in the vascular wall tissues of TAD patients, ECM shows obvious abnormalities [8].…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies confirmed that phenotypic transformation of SMCs from the contractile to synthetic type is one of the typical events in the development of AD (27,28). The increase of migration ability is the embodiment of the synthetic type, accompanied by the secretion of matrix metalloproteinases and a decline in contractile capability (29,30). Thus, downregulated FLNA expression in AD patients may be involved in the regulation of migration ability, phenotype transformation, and ECM secretion by VSMCs.…”
Section: Discussionmentioning
confidence: 68%
“…Aortic dissection specimens were obtained during the Bentall procedures or other large vessel replacements of TAD patients. Patients with traumatic aortic injury, inflammatory aortic disease, Ehlers-Danlos syndrome, Marfan syndrome, and other connective tissue disorders were excluded (17). Control aortic specimens were obtained from patients who underwent aortic valve replacement without vascular wall lesion.…”
Section: Tissue Collectionmentioning
confidence: 99%